Weight Training Effect of Multi-Poundage System on Bench Press Ability - Nolfie Piri; Ellen Bernadeth Lomboan; Fredrik Alfrets Makadada (Britain International for Academic Research (BIAR) Publisher, 2019)
This study discusses about find out how weight training effect of multi-poundage system on bench press ability in students majoring in coaching education. The research design used in this study refers to the experimental design using